Emerging biotechnologies and non-thermal technologies for winemaking in a context of global warming - Comuzzo, Piergiorgio; del Fresno, Juan Manuel; Voce, Sabrina; Loira, Iris; Morata, Antonio (Frontiers in Microbiology, 2023)
In the current situation, wine areas are affected by several problems in a context of global warming: asymmetric maturities, pH increasing, high alcohol degree and flat wines with low freshness and poor aroma profile. The use of emerging biotechnologies allows to control or manage such problems. Emerging non-Saccharomyces as Lachancea thermotolerans are very useful for controlling pH by the formation of stable lactic acid from sugars with a slight concomitant alcohol reduction. Lower pH improves freshness increasing simultaneously microbiological stability. The use of Hanseniaspora spp. (specially H. vineae and H. opuntiae) or Metschnikowia pulcherrima promotes a better aroma complexity and improves wine sensory profile by the expression of a more complex metabolic pattern and the release of extracellular enzymes. Some of them are also compatible or synergic with the acidification by L. thermotolerans, and M. pulcherrima is an interesting biotool for reductive winemaking and bioprotection. The use of bioprotection is a powerful tool in this context, allowing oxidation control by oxygen depletion, the inhibition of some wild microorganisms, improving the implantation of some starters and limiting SO 2 . This can be complemented with the use of reductive yeast derivatives with high contents of reducing peptides and relevant compounds such as glutathione that also are interesting to reduce SO 2 . Finally, the use of emerging nonthermal technologies as Ultra High-Pressure Homogenization (UHPH) and Pulsed Light (PL) increases wine stability by microbial control and inactivation of oxidative enzymes, improving the implantation of emerging non-Saccharomyces and lowering SO 2 additions.